Xray detector based on bulk micromachined photodiode - Rocha, J. G. (2002)
This paper reports the design, fabrication, assembly and testing of a xray detector based on a bulk micromachined photodiode (BMMPD) with a cavity filled with a scintillating crystal. The xray photons that reach the detector are first converted to visible light by the scintillating crystal. The visible light is then detected by the BMMPD, producing an electric current whose value is proportional to the incident xray intensity. The tests are done using a xray tube powered with a voltage of 35 kV, and a current ranging from 0 mA to 1 mA. With this setup, very promising results were obtained. may be divided into three classes: Dose reduction, image processing and display in real time, and flexibility in image storage and retrieval. The first advantage of digital radiography is the possibility of dose reduction. In conventional radiology, the dose is determined by the sensitivity of